Cell Cycle-Dependent Expression Dynamics of G1/S Specific Cyclin, Cellulose Synthase and Cellulase in the Dinoflagellate Prorocentrum donghaiense - Shi, Xinguo; Ma, Minglei; Lin, Senjie (Frontiers in Microbiology, 2017)
Dinoflagellates undergo a typical eukaryotic cell cycle consisting of G1, S, G2, and M phases and some of the typical cell cycle related genes have been computationally identified. However, very few of these genes have been experimentally linked to the cell cycle phases. Besides, although thecate dinoflagellates are known to possess theca composed of cellulose, information on cellulose synthesis and degradation associated with the cell cycle is also limited. In this study, we isolated G1/S cyclin, cellulose synthase and cellulase encoding genes in dinoflagellate Prorocentrum donghaiense. Further, using reverse transcription quantitative PCR (RT-qPCR), we characterized the expression profiles of the three genes throughout the cell cycle. All three showed clear expression dynamics throughout the cell cycle, with fold changes of 26, 2.4 and 9.3 for G1/S cyclin, cellulose synthase and cellulase gene, respectively. The transcript abundance of G1/S cyclin increased in late G1 phase and dropped in early S phase, indicating that this protein is involved in the G1/S transition. Throughout the cell cycle, the average transcript level of cellulose synthase was 4.5 fold higher than that of cellulase. Cellulose synthase and cellulase gene expressions showed peak transcript abundances at middle G1 phase and G2M phase, respectively, indicating the respective roles of these enzymes in the growth of newly divided cells and in cytokinesis. Our results suggest that G1/S cyclin, cellulase, and cellulose synthase genes associated with G1/S transition, G2M, and G1 phases of the cell cycle and are candidates of biomarkers for assessing growth status of P. donghaiense.